Donasi Online sebagai Budaya Siber Generasi Milenial - Muslimah, Fauziah (LPPM Universitas Bina Sarana Informatika, 2020)
New media is currently a new breakthrough for information and communication technology. with this new media, anyone can communicate through anything, anytime, anywhere. Therefore, new media offers easy communication access to exchange information for netizens or what are often known as netizens. Regarding new media, Denis McQuail in his book entitled The Theory of Mass Communication (2011) states that the main characteristic of new media is that media that allows is interconnectedness in helping communication between users. In addition, new media also provides easy access to individual audiences as message recipients and senders, its interactivity, and the various uses of these media make new media have an open character and can be used everywhere. But, on the other hand, the use of this new media is a phenomenon worth worrying about. This is related to new media which is used only as a place to show off themselves or even spread fake news content or hoaxes on social media. Meanwhile, on the other hand, there are also netizens who use new media to spread goodness and even create a new trend among social media users. This trend has become a new value for Indonesian netizens, thus becoming a new culture for the online community in this country. The trend is online hills. Udunan here means an outcome or donation made together online by social media users in cyberspace. This activity is routinely carried out and well organized, so that online donations also reach many people through donations sent to various humanitarian aid projects throughout Indonesia, even abroad. In Indonesia, online udunan is growing. Especially with the presence of a website and online application that makes it easier for people to make donations via the internet. This has become a new phenomenon where people have changed their behavior, from making direct donations to donating to the construction of mosques, orphanages, poor people and nearby orphans, now they can set aside their money through online applications available. in your hand (pitar cellphone). Furthermore, based on this phenomenon, this study will focus on users of online donation applications. This study uses a virtual ethnographic study. Meanwhile, virtual ethnography study is a method of ethnography that is carried out to see firsthand matters related to the phenomenon and culture or culture of media users in cyberspace or cyberspace. Then, as a culture or culture and cultural artifacts, cyberspace or cyberspace for virtual ethnographic researchers, researchers can approach several objects or phenomena that exist and occur on the internet (Nasrullah, 2017). Kitabisa.com, Act.id, and takrim-alquran.org are three online sites that will be the focus of this research. The nature of the website's activities are online donation media that comes from private institutions, national zakat institutions, and community social institutions. Based on the method of observation, documentation (related literature), and interviews with the three informants, millennials who actively use the internet to communicate and get information tend to use online media and social media as a form of making it easier to carry out an activity. Not only communicating and exchanging information, Generation Y is also actively using online media to facilitate other activities, such as buying and selling (online shopping) and even donating or donating. The researcher identified that of the three informants there were three main motives for using online donation media for the millennial generation. These motives are social motives, feelings motives, and expression motives. The social motive related to the reason for the millennials generation to donate online is because it is to help others. Meanwhile, the feeling motive is their reason for self-gratification and pleasure. Lastly, expression motive. In the era of technology and information that is increasingly developing today, making millennials active in social media. Keywords: Donation, Online, Millennial, Social Media.